GAME CONCEPT OF DECISION MAKING IN ECONOMIC CHALLENGES WITH RANDOM OUTCOMES - Victor A. Vlasov; Sergey I. Alexeev; Raisa I. Soroka; Andrew O. Tolokonski (Статистика и экономика)
This article considers discrete (game) multiple decision-making process, which consists of a sequence of independent tours. In each round of the tour the results are of chance. The article identifies best game strategy.